2002
DOI: 10.1046/j.1468-3083.2002.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mastocytosis with onset in children and adults

Abstract: We confirm the incidence of onset of mastocytosis previously reported in the literature. We conclude that childhood onset mastocytosis is much less transitory than generally is assumed, although improvement occurs in the majority of cases. Symptomatology and clinical course of adult onset mastocytosis is less severe than suggested in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 21 publications
4
49
0
5
Order By: Relevance
“…Hannaford and Rogers [10] reported 3 cases with DCM among 173 pediatric patients with mastocytosis. We reported 2 cases of DCM among 65 cases of childhood onset mastocytosis in 2002 [7]. To our knowledge the present case study is the largest series of DCM with two different variants of clinical presentations reported.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Hannaford and Rogers [10] reported 3 cases with DCM among 173 pediatric patients with mastocytosis. We reported 2 cases of DCM among 65 cases of childhood onset mastocytosis in 2002 [7]. To our knowledge the present case study is the largest series of DCM with two different variants of clinical presentations reported.…”
Section: Discussionmentioning
confidence: 83%
“…Maculopapular mastocytosis is the commonest variant, but this may depend on the setting of the institution. The prognosis of pediatric mastocytosis is mostly good [5,7,8]. The visible cutaneous abnormalities in CM are frequently of major concern to the patients and their family.…”
Section: Introductionmentioning
confidence: 99%
“…A small 2004 study in which people were given oral doses of the fern extract after exposure to ultraviolet light found that their skin was less red and had fewer sunburnt cells than subjects not given the extract 3,4 . And a 1997 study looked for markers of cell damage caused by exposure to ultraviolet light in ten volunteers who ingested the fern extract 5 .…”
Section: Less Radicalmentioning
confidence: 99%
“…Çocukluk çağında, yetişkinlerde gözlenenin tersine klinik çok daha selim gidişlidir ve kendi kendini sınırlar (8) .…”
Section: Introductionunclassified